Development of E-Module of Science Based on Bondowoso Ethnoscience on Vibration and Wave Material - Damayanti, Silvia Qaulina; Supeno, Supeno; Asyiah, Iis Nur (Universitas Pendidikan Mandalika, 2025)
This study aims to produce Bondowoso ethnoscience-based science e-modules on vibration and wave materials suitable for use in learning activities. The development research uses a 4D model to define, design, develop, and disseminate. Data collection is done through observation, interviews, and expert validation. Interviews were conducted with 8th-grade science teachers and Bondowoso art activists. Validation was carried out by providing validation sheets and developing products for validators. The results of this study indicate that the Bondowoso ethnoscience-based science e-module has a high feasibility level, as evidenced by the average validation score of 89.5%, and the interpretation of validity is very valid. The validity of media feasibility is 87.5%, the validity of material feasibility is 91.7%, and the validity of language feasibility is 89.3%. Based on these results, it can be concluded that the Bondowoso ethnoscience-based science e-module on vibration and wave material is very feasible to use in learning.